Promotion of angiogenesis in vitro by Astragalus polysaccharide via activation of TLR4 signaling pathway. Issue 10 (22nd July 2022) - Qiu, Huiqing; Zhang, Liyan; He, Xinqi; Wei, Yusen; Wang, Miaoran; Ma, Bin; Hu, Dailun; Shi, Zhongli
Abstract: During the implantation of functional tissue‐engineered constructs for treating bone defects, a functional vascular network is critical for the survival of the construct. One strategy to achieve rapid angiogenesis for this application is the co‐culture of outgrowth endothelial cells (OECs) and primary human osteoblasts (POBs) within a scaffold prior to implantation. In the present study, we aim to investigate whether Astragalus polysaccharide (APS) promotes angiogenesis or vascularization via the TLR4 signaling pathway in a co‐culture of OECs and POBs. The co‐cultures were treated with various concentrations of APS for 24 h and, subsequently, another 7 days, followed by CD31 staining and analysis of micro‐vessel‐formation areas using software. Additionally, APS (0.4 mg/ml for 24 h) was added to monocultures of OECs or POBs for evaluating proliferation, apoptosis, angiogenesis, osteogenesis, TLR4 signaling pathway, and inflammatory cytokine release. We found that APS promoted angiogenesis in the co‐culture at the optimal concentration of 0.4 mg/ml. TLR4 activation by APS up‐regulated the expression level of TLR4/MyD88 and enhanced angiogenesis and osteogenesis in monocultures of OECs and POBs. The levels of E‐selectin adhesion molecules, three cytokines (IL‐6, TNF‐α, and IFN‐γ), and VEGF and PDGF‐BB, which can induce angiogenesis, increased significantly ( p  < .05) following APS treatment. Therefore, APS appears to promote angiogenesis and ossification in the co‐culture system via the TLR4 signaling pathway. Practical applications: This study demonstrates that APS may promote angiogenesis and osteocyte proliferation in OEC and POB co‐culture systems through the MyD88‐dependent TLR4 signaling pathway. APS might represent a potential therapeutic strategy in tissue‐engineered bone implantation for the treatment of large bone defects; additionally, it has the advantage of safety, as it exhibits low or no side effects. In the future, it is expected to be used in vitro for the construction of tissue‐engineered bone and in vivo after implantation in patients with bone defects for promoting rapid vascularization and ossification of tissue‐engineered bone and early fusion with the recipient's bone. In addition, as a food additive, Astragalus membranaceus can be used as a tonic material in patients recovering from a fracture for promoting blood‐vessel formation at the fracture site and fracture recovery. Combining traditional Chinese medicine with tissue engineering can provide further strategies for promoting the development of regenerative medicine. Abstract : Astragalus polysaccharide not only upregulated the expression of angiogenic factors in OECs and osteotropic factors in POBs but also promoted angiogenesis in their co‐culture system. This effect may be achieved by activating TLR4‐MyD88 dependent pathway.